Original article Phenotypic diversity resulting from a point mutation - Sypecka, Joanna; Domańska-Janik, Krystyna (Folia Neuropathologica, 2006)
Paralytic tremor (pt), a hereditary neurological disorder of rabbits, is a recessive, X-linked point mutation in exon 2 of the plp gene, responsible for substitution of 38 His by Glu in the PLP molecule. Pt genotype is expressed in a range of phenotypes, distinguished by the severity of neurological symptoms. Variable course of the disease, from totally asymptomatic to serious disorder, is observed even within the offspring of one breeding pair. The two most typical phenotypes have been chosen for the studies: one representing mild course of the disease and the other reflecting the most severe course. Since previous developmental studies proved that myelination is not only deficient but also delayed in pt rabbits, the age groups of animals have been selected with the aim of spanning the period of most active myelinogenesis. As revealed by experiments, the degree of CNS hypomyelination, which is the main future of pt mutation, is highest in the most affected animals. The amounts of mutated gene products, PLP and DM-20, examined both at mRNA and protein levels, exhibited a strong dependence on phenotype. Down-regulation of MBP and CNP was also observed. In contrast, MAG expression was normal or only slightly changed in mutants. The results lead to the conclusion that pt mutation in the plp gene affects a panel of events that governs myelinogenesis and is modulated in each individual that is manifested by gradation of neurological symptoms.